Do parents matter? Intergenerational ties and fertility preferences in a low-fertility context. (December 2015) - Ji, Yingchun; Chen, Feinian; Cai, Yong; Zheng, Zhenzhen
Using data from the Jiangsu Fertility Intention and Behavior Study (JFIBS), this study examines multidimensional influences of intergenerational ties on married women's intended and ideal family size in Jiangsu Province, China, an extremely low-fertility setting. Our results suggest that preference for a grandson and a granddaughter, and a woman's willingness to take advice from the parental generation promotes fertility motivation. In addition, potential (or actual) childcare provision from grandparents shifts fertility intention upward. Some family influences (e.g. family size of origin) tend to be more salient from parents-in-law than from parents, reflecting the patrilineal and patriarchal tradition in China. At the same time, we do not find any pronatalistic effect of co-residence with parents or parents-in-law.